Evaluation of education quality components - Godsmohammadi, Amir; Nourabadi, Soolmaz (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The aim of the present study in the upper elementary school is to investigate the components of education quality that which one-teacher and multi-teacher methods are more effective from the Iranian teachers' point of view. This research is applied method in terms of purpose that was done through survey method. The results indicate that the quality of one-teacher teaching in upper elementary course is moderate to low because the average obtained is 2.96, less than the hypothetical average of number 3. Also, the quality of multi-teacher teaching in upper elementary course is moderate to high because the average obtained is 4.09, more than the hypothetical average. Therefore, considering the findings and analysis of the information that obtained in most components related to the quality of teaching, there are obvious differences between the one-teacher and multi-teacher in quality of courses, and the multi-teacher method is better than the one-teacher method in the upper elementary school.